Abordagem investigativa sobre a sindrome do respirador oral em Belém do Pará - LOPES, Luiz Renato Oliveira (2020)
Comprehensive health care for the population is a basic guideline of the Unified Health System and access to information is the central aspect of this care. The importance of user empowerment is key to making it the protagonist of care and having it as an ally in the caring process. The dynamics of health services result from an interaction of factors, such as the need and the perception of this action from the perspective of the user. Therefore, it is incumbent upon us to study the knowledge about Oral Respiratory Syndrome (ORS) if it is disclosed. ORS is characterized by obstruction of the upper airways that leads the patient to the habit of breathing through the mouth, with a large number of etiologies both intrinsic and extrinsic to the nose, with characteristic signs and symptoms, further compromising the pediatric range, and causing repercussions which may be local (upper airways and ears) or systemic. The present work seeks to investigate the knowledge of the population of Belém do Pará about ORS and to guide it about this syndrome. Most respondents were unaware of ORS, many had the symptoms suggestive of the disease, or knew of a family member, and approximately half of the respondents were aware of who would be the most appropriate health care provider to make the diagnosis and treatment.